Instructions: - R. Joseph Rodríguez (University of Oklahoma Libraries, 2023)
In these extraordinary times, we felt we would start this issue on censorship with a poem. Much that is going on in our country is cacaphony; Joseph R. Rodríguez' poem makes the noise more legible.